My colorful sketches from scratch: molecular imaging - Nordin, Abdul Jalil (Universiti Putra Malaysia Press, 2013)
Have you heard the story about the tortoise? Only through perseverance did it manage to get to the boat. It is up to you how much you are willing to sacrifice and how long you want to fight before you obtain your goals. If you decide to pursue a road, then make sure you stick with it until the very end. I believe that these life lessons are the key to fulfillment. PET, CT, and MR are molecular imaging tools. Combined PET-CT has evolved into an established clinical tool in diagnostic imaging. The facility need to be optimized and standardized to help improving the clinical management of patients. "MY COLORFUL SKETCHES FROM SCRATCH" Molecular Imaging is about the struggle on establishing the specialized field of Molecular Imaging, PET-CT in particular, through academia and international networking. I hope my story will inspire those out there looking for their own niche be it academic or non-academic encounter.